Pathophysiology, Diagnosis, and Management of Hypertension in the Elderly - Glazier, James J. (International Journal of Angiology, 2022)
There is a high prevalence of systemic arterial hypertension in the elderly; 70% of adults >65 years have this disease. A key mechanism in the development of hypertension in the elderly is increased arterial stiffness. This accounts for the increase in systolic blood pressure and pulse pressure and fall in diastolic blood pressure (isolated systolic hypertension) that are commonly seen in the elderly, compared with younger persons. The diagnosis of hypertension is made on the basis of in-office blood pressure measurements together with ambulatory and home blood pressure recordings. Lifestyle changes are the cornerstone of management of hypertension.Comprehensive guidelines regarding blood pressure threshold at which to start pharmacotherapy as well as target blood pressure levels have been issued by both European and American professional bodies. In recent years, there has been considerable interest in intensive lowering of blood pressure in older patients with hypertension. Several large, randomized controlled trials have suggested that a strategy of aiming for a target systolic blood pressure of <120 mm Hg (intensive treatment) rather than a target of <140 mm Hg (standard treatment) results in significant reduction in the incidence of adverse cardiovascular events and total mortality. A systolic blood pressure treatment of <130 mm Hg should be considered favorably in non-institutionalized, ambulatory, free living older patients. In contrast, in the older patient with a high burden of comorbidities and limited life expectancy, an individualized team-based approach, based on clinical judgment and patient preference should be adopted. An increasing body of evidence for older adults with hypertension suggests that intensive blood pressure lowering may prevent or at least partially prevent cognitive decline.
Keywords: hypertension; elderly patient; arterial stiffness; intensive blood pressure lowering; mild cognitive impairment; pseudohypertension